ALLERGIC REACTIONS AND MEDICINAL PRODUCTS: CONTEMPORARY PRESENTATIONS - Yomgurova Ozoda Rajabturdievna (Galaxy International Interdisciplinary Research Journal, 2023)
More than 7% of the population suffers from drug allergies. Cases of severe life-threatening allergic reactions have been reported. The review presents modern views on the mechanisms of development of drug immune hypersensitivity, describes the main clinical forms and existing methods for diagnosing drug allergies. Specific diagnosis of drug allergy is carried out using in vivo tests (prick tests, intradermal testing, patch tests, provocative tests) and in vitro (determination of specific IgE to drugs, basophil activation tests, leukocyte blast transformation reactions, quantitative determination of cytokines and other proteins , such as granzyme and tryptase in peripheral blood).